Environmental DNA Based Surveillance for the Highly Invasive Carpet Sea Squirt Didemnum vexillum: A Targeted Single-Species Approach - Iveta Matejusova; Jennifer Graham; Fiona Bland; Jean-Pierre Lacaze; Guillaume Herman; Lyndsay Brown; Eric Dalgarno; John D. Bishop; Jenni E. Kakkonen; Kirsty F. Smith; Alex Douglas (Frontiers in Marine Science, 2021)
The presence and diversity of marine non-native species, the number of new invasions, and the impact on native communities and habitats are important metrics used to assess the health of marine ecosystems. Monitoring for marine non-native species, using traditional approaches such as rapid assessment surveys (RASs), requires taxonomic expertise and may still fail to detect rare or inconspicuous species. This study reports a validation process for a quantitative PCR (qPCR) assay based on the cytochrome oxidase 1 gene, designed to detect highly invasive tunicate Didemnum vexillum by targeting environmental DNA (eDNA) present in water samples. The D. vexillum qPCR assay showed high sensitivity, with the threshold limit of detection (LOD) and modeled LOD3 (based on triplicate qPCR reactions) estimated as 9.187 and 1.117 copies reaction –1 , respectively and the limit of quantification (LOQ) was calculated as 18 copies reaction –1 . Analyses of water samples collected from selected Pacific oyster farms and recreational marinas in Scotland showed 100% concordance between the historical data on presence of D. vexillum from RASs and detection of D. vexillum eDNA. Consistency of detection of D. vexillum eDNA among different sampling points within each infected sampling site varied, ranging between 100% positive throughout the site to some sampling points testing “negative” or only as “suspected” for D. vexillum . Sites with lower within-site detection consistency included sites with a low density of D. vexillum as reported by RASs or were sites undergoing D. vexillum management. The present pilot monitoring program demonstrates the potential to generate important data on presence of D. vexillum . This program will be scaled up across large geographic regions and used in the first instance to focus and target the traditional RASs to D. vexillum eDNA-positive sites in a cost-effective way, with an aim to verify the species presence by visual observation and direct Sanger sequencing of positive qPCR products.